2005
DOI: 10.1111/j.1471-0528.2004.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour

Abstract: Objective To assess whether intrapartum acidosis affects specific components of fetal heart rate variability.Design Prospective clinical study.Setting Twelve Nordic delivery units.Subjects Fetal heart rate variability was studied in 334 fetuses divided into two groups according to cord pH value: the acidotic group (cord arterial pH <7.05 at birth, n ¼ 15) and the control group (cord arterial pH !7.05 at birth, n ¼ 319). Methods In spectral analysis of fetal heart rate variability, frequencies were integrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 33 publications
4
82
1
Order By: Relevance
“…[30][31][32] Studies from Siira et al and Salamalekis et al showed a predominant increase in the low-frequency domain and, therefore, a higher low-to high-frequency ratio in acidotic fetuses, consistent with the increase in sympathetic system activity induced by hypoxia. 16,19,31,32 Interestingly, one of the multifractal parameter we studied (zeta(2)), which is related to low-to highfrequency ratio, also showed a predominant increase in sympathetic component when fetal acidosis developed. [31][32][33] One of the strengths of multifractal analysis is also to provide multiple parameters to explore signal variability, particularly for complex signals that can definitely not be appropriately described using only one parameter.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…[30][31][32] Studies from Siira et al and Salamalekis et al showed a predominant increase in the low-frequency domain and, therefore, a higher low-to high-frequency ratio in acidotic fetuses, consistent with the increase in sympathetic system activity induced by hypoxia. 16,19,31,32 Interestingly, one of the multifractal parameter we studied (zeta(2)), which is related to low-to highfrequency ratio, also showed a predominant increase in sympathetic component when fetal acidosis developed. [31][32][33] One of the strengths of multifractal analysis is also to provide multiple parameters to explore signal variability, particularly for complex signals that can definitely not be appropriately described using only one parameter.…”
Section: Discussionmentioning
confidence: 86%
“…Multifractal analysis has the strength to reach results consistent with previous studies about variability using other mathematical methods, such as the classical spectral analysis, and to provide additional information that could help in discriminating fetuses with acidosis from nonacidotic fetuses. 2,7,16,18 Consistent with previous studies and physiopathologic mechanisms, the results of this study showed that variability is lower in the acidotic fetuses when compared with the nonacidotic fetuses as demonstrated by higher values of C 1 , h min , h Max , and zeta(2) in group C. 2,7,16,18 Moreover, multifractal analysis focuses on characterizing the evolution of signal variability in a collection of windows of growing size, identified by the method itself according to the intrinsic data characteristics and not chosen a priori. Our results showed that windows of interest for multifractal analysis ranged from 4 to 64 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations